PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPEMIMPINAN TRANSAKSIONAL DAN KOMUNIKASI INTERNAL TERHADAP KINERJA KARYAWAN DI PT. JAYABRIX INDONESIA LAMONGAN - Miftahul Huda; Moh. Azus Shony Azar (LPPM UNISDA, 2018)
Human resources is one of the important factors in a company. This research to analyze and find out how much Transformational Leadership, Transactional Leadership and Internal Communication on Employee Performance. The sampling technique used was field research using incidental samples. The sample of this study was 43 employees working at PT. Jayabrix Indonesia Lamongan who then made respondents and filled out questionnaire sheets that have been provided by the author. The results showed based on the F test stating that there was an influence of Transformational Leadership, Transactional Leadership and Internal Communication simultaneously on employee performance of 35,230, t test stated that the Transformational Leadership variable was 2,054 Transactional Leadership was 2,500 and Internal Communication was 4,382 which was the dominant variable influencing Employee performance. Based on the coefficient of determination test, it can be seen that the R2 value is 72%, meaning that Transformational Leadership, Transactional Leadership and Internal Communication to Employee Performance is 72%, the remaining 28% is influenced by other factors outside this research variable.